2014
DOI: 10.1371/journal.pone.0088083
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Staphylococcus aureus CC398 Reveals a Sub-Lineage Epidemiologically Associated with Infections in Horses

Abstract: In the early 2000s, a particular MRSA clonal complex (CC398) was found mainly in pigs and pig farmers in Europe. Since then, CC398 has been detected among a wide variety of animal species worldwide. We investigated the population structure of CC398 through mutation discovery at 97 genetic housekeeping loci, which are distributed along the CC398 chromosome within 195 CC398 isolates, collected from various countries and host species, including humans. Most of the isolates in this collection were received from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 79 publications
(79 reference statements)
2
34
0
1
Order By: Relevance
“…Patient-to-patient transmission and outbreaks within equine hospitals as well as zoonotic transmission have been documented1819282930. Recently, an epidemic subclone of CC398 MRSA was shown to have spread within and between equine hospitals23. This subclone consisted almost exclusively of spa-type t011 strains, which in our study had a high prevalence of LukPQ.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Patient-to-patient transmission and outbreaks within equine hospitals as well as zoonotic transmission have been documented1819282930. Recently, an epidemic subclone of CC398 MRSA was shown to have spread within and between equine hospitals23. This subclone consisted almost exclusively of spa-type t011 strains, which in our study had a high prevalence of LukPQ.…”
Section: Discussionsupporting
confidence: 48%
“…Between isolate collections, the prevalence of lukPQ differed considerably. In the Dutch collection LukPQ was found in 25 of 74 isolates (34%); interestingly this included 11 out of 21 isolates (52%) from the spa -type t011 (CC398) - a lineage that has been reported to be specifically associated with horses23.…”
Section: Resultsmentioning
confidence: 99%
“…The avian prophage genes were not detected in any of the UK isolates, including the turkey MRSA isolate (APHA01). Presence of the φAVβ prophage in MSSA but not MRSA in this and other studies (Argudin et al, 2013; Abdelbary et al, 2014) may suggest an association between the φAVβ prophage and MSSA isolates, which requires further investigation.…”
Section: Discussionmentioning
confidence: 53%
“…None of the isolates explored in this study carried any human associated virulence genes, in concordance with a previous study (Price et al, 2012) and the above suggestions. However, SAAV_2008 and SAAV_2009 virulence genes associated with the avian adapted φAVβ prophage that have been reported by several authors (Price et al, 2012; Argudin et al, 2013; Abdelbary et al, 2014), were identified in nine MSSA isolates from the US from turkeys and pigs. The avian prophage genes were not detected in any of the UK isolates, including the turkey MRSA isolate (APHA01).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, it has been suggested that the detection of the same spa type in isolates belonging to two different sequence types is due to the exchange of genetic material amongst clones of animal origin (Camoez et al, 2013). Moreover, t899 isolates have been recovered not only in pigs, but also in other animals, such as cattle, horses or poultry (Abdelbary et al, 2014;Friese et al, 2013;Graveland et al, 2010;Smith & Pearson, 2011). Very recently, it has been also detected an MRSA strain ST398 of the spa type t4358 in a food sample of chichen origin in Tunisia (Chairat et al, 2015).…”
Section: Discussionmentioning
confidence: 99%